FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PETANI KARET (Studi Kasus di Desa Getas Kecamatan Singorojo Kabupaten Kendal) - Agus Stiawan; Sri Wahyuningsih; Eka Dewi Nurjayanti (MEDIAGRO, 2014)
Rubber is one of the main commodity crops are widely cultivated by people. Rubber farming is one of source income for rubber farmers in Getas Village, Singorojo District, Kendal Regency. The aim of this study is to: 1. Determine the factors affecting farmers' income in Getas Village, Singorojo District, Kendal, 2) determine the level of revenue and income from rubber farming in in Getas Village, Singorojo District, Kendal, 3) determine the feasibility of rubber  farming in Getas Village, Singorojo District, Kendal. There are 42 total sample respondents. The method used in this study is descriptive analytical method which using purposive sampling and analysis of data with multiple linear regression. Based on the regression analysis, it was found R Square value of  0,822, which means that the income of rubber farmers affected by the land area, number of workers, farmers age, education level, age of the plant and fertilizer was 82,2%, and the remaining of 17,8 was influenced by other variables out of the research model. From the results of the regression analysis, found that the significant variables were the land area and fertilizer. Based on the t test, the land area had a value of t count, 4,686 and the fertilizer variable had a value of t count, 5,794. The t value was greater than t table, 2,438, which means that the land area variable and fertilizer were significantly affected the rubber farmers' income by 99 percent significance level. While for the variables of the number of workers, farmers age, education level and age of the plant did not significantly affect the income. The results obtained by an average of Rp 1.244.759,52 and the median income for Rp. 1.153.025,74 within one month. Based on analysis of RC ratio, it is obtained value of RC ratio of 2,5 which means farming is economically viable.  By looking at the results of the research, it is expected that the farmers are able to maximize both the use of land area and fertilizing because it showed that both variables were significantly affected to the income.   Keywords: fertilizer, income, land area, rubber.